2020
DOI: 10.1186/s12887-020-1946-0
|View full text |Cite
|
Sign up to set email alerts
|

How many words are Australian children hearing in the first year of life?

Abstract: Background: There is evidence that parents from more socioeconomically disadvantaged backgrounds engage in fewer verbal interactions with their child than more advantaged parents. This leads to the so-called, '30 millionword gap'. This study aims to investigate the number of words children hear and the number of vocalizations children produce in their first year of life and examines whether these aspects of the early language home environment differ by maternal education. Methods: Mothers were recruited into a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Using this stringent definition of language input, speech from other family members directed to the target child and speech from a primary caregiver directed to a nearby sibling were not counted towards the child's language input. On the other hand, many studies (such as Brushe et al, 2020) use Language Environment Analysis software (LENA, Greenwood et al, 2011), which uses LENA's proprietary algorithm to automatically estimate the number of words spoken by all adults near (but not necessarily directly to) the target child. These dramatically different definitions demonstrate that there is no clear consensus on what "counts" as language input.…”
Section: Measuring Language Inputmentioning
confidence: 99%
“…Using this stringent definition of language input, speech from other family members directed to the target child and speech from a primary caregiver directed to a nearby sibling were not counted towards the child's language input. On the other hand, many studies (such as Brushe et al, 2020) use Language Environment Analysis software (LENA, Greenwood et al, 2011), which uses LENA's proprietary algorithm to automatically estimate the number of words spoken by all adults near (but not necessarily directly to) the target child. These dramatically different definitions demonstrate that there is no clear consensus on what "counts" as language input.…”
Section: Measuring Language Inputmentioning
confidence: 99%
“…The LiLO study started collecting language data in the home, involving day-long recordings, when the children were 6 months old with data collection occurring every 6 months, until their first year of schooling, around age 5. We previously reported that when children were 6 and 12 months old there were no meaningful differences in any measure of parentchild talk between maternal education groups [12]. There was large variability, with high and low talkers within both education groups.…”
Section: Introductionmentioning
confidence: 81%
“…A home visit occurred with each family within 2 months of the child's 6, 12 and 18 month birthdates. Data collection procedures have been previously described, with processes remaining consistent at each wave for all families in the study [12].…”
Section: Participantsmentioning
confidence: 99%
“…There is now broad acceptance of this social gradient for language development as there is for many other aspects of child development (Marmot, 2010;Maggi et al, 2010) and some evidence that these gaps are evident for language may not be apparent at 12 months (Brushe et al, 2020) but has emerged by 18 months of age (Brushe et al, 2021;Fernald et al, 2013). Concerns expressed about the Hart and Risley study (Fernald & Weisleder, 2015;Kuchirko, 2017) focus on both the analysis and the interpretation of their findings and specifically whether talking more to children or perhaps interacting with them more effectively is, in itself, likely to be enough to redress any imbalance (Wasik & Hindman, 2015).…”
Section: Hart and Risley Concludedmentioning
confidence: 99%